2009
DOI: 10.1038/nsmb.1570
|View full text |Cite
|
Sign up to set email alerts
|

Polyglutamine disruption of the huntingtin exon 1 N terminus triggers a complex aggregation mechanism

Abstract: Simple polyglutamine (polyQ) peptides aggregate in vitro via a nucleated growth pathway directly yielding amyloid-like aggregates. We show here that the 17 amino acid flanking sequence (httNT) N-terminal to the polyQ in the toxic huntingtin exon1 fragment imparts onto this peptide a complex alternative aggregation mechanism. In isolation the httNT peptide is a compact coil that resists aggregation. When polyQ is fused to this sequence, it induces in httNT, in a repeat-length dependent fashion, a more extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

104
825
6
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 401 publications
(937 citation statements)
references
References 60 publications
104
825
6
2
Order By: Relevance
“…Secondary chemical shift (SCS) values for H16 at pH 6.5 were computed as the difference between the measured chemical shifts and their amino acid specific random‐coil values using neighbor amino acid sequence corrections employing a well‐established random‐coil chemical‐shift database 22. Figure 2 g, which displays the SCS difference between Cα and Cβ for htt exon1, indicates that the 17 N‐terminal residues (N17) have a strong propensity for α‐helical structure that increases when approaching the HR, which is in agreement with previous NMR studies 16, 23. Along the poly‐Q tract, a systematic decrease in helical propensity is observed, with Q32 presenting random‐coil chemical shifts.…”
supporting
confidence: 87%
“…Secondary chemical shift (SCS) values for H16 at pH 6.5 were computed as the difference between the measured chemical shifts and their amino acid specific random‐coil values using neighbor amino acid sequence corrections employing a well‐established random‐coil chemical‐shift database 22. Figure 2 g, which displays the SCS difference between Cα and Cβ for htt exon1, indicates that the 17 N‐terminal residues (N17) have a strong propensity for α‐helical structure that increases when approaching the HR, which is in agreement with previous NMR studies 16, 23. Along the poly‐Q tract, a systematic decrease in helical propensity is observed, with Q32 presenting random‐coil chemical shifts.…”
supporting
confidence: 87%
“…C-Terminal Polyproline Inhibits the Aggregation of Q 20 -P 10 Without Altering the Aggregation Mechanism Proline-rich segments often follow the polyQ sequence in many proteins involved in neurodegenerative diseases (17,33). Although the NT17 peptide addition encourages aggregation, the proline-rich terminus at the C end inhibits aggregation (17,(34)(35)(36).…”
Section: N-terminal Region Facilitates the Aggregation Of Nt 17 -Q 20mentioning
confidence: 99%
“…Using the associative memory, water-mediated interactions, structure and energy model (AWSEM), previous simulations by our group have successfully explained how the change of critical nucleus size arises from the differences in the propensity of monomeric polyQ repeats of different lengths to form β-hairpins: the longer repeats fold into hairpins intramolecularly before they aggregate (9). The aggregation of the diseasecausing peptide is, however, further complicated by the presence of flanking amino acid sequences in fragments encoded by HTT exon 1. Experiments indicate that the addition of NT17 at the N terminus of polyQ enormously accelerates the aggregation, probably by encouraging the formation of prefibrillar oligomers (10)(11)(12)(13)(14)(15)(16), whereas the addition of the proline-rich region at the C terminus decreases the rate of aggregation apparently without changing fundamentally the mechanism (10,16,17). Structural characterization of the aggregates (13,14,(18)(19)(20) has shown that, even when there are flanking sequences, polyQ remains the fiber core and adopts a β-hairpin conformation.…”
mentioning
confidence: 99%
“…More recent studies, however, indicate that polyQ flanking sequences, rather than the polyQ tracts themselves, initiate spontaneous HTT protein aggregation (Saunders and Bottomley 2009). For instance, it was shown that the first 17 amino acids in HTT, which adopt an α-helical conformation, can initiate the spontaneous aggregation of pathogenic polyQ tracts in cell-free assays (Thakur et al 2009). The importance of this polyQ flanking sequence for HTT misfolding is supported by biochemical studies with a chaperonin, which directly binds to the first 17 amino acids of HTT and blocks the de novo aggregation of N-terminal HTT fragments (Tam et al 2009).…”
mentioning
confidence: 99%